Biology and intraspecific competition of tachinids on the host Diatraea saccharalis under laboratory conditions - de Almeida, Luiz Carlos; Araújo, José Ribeiro de; Botelho, Paulo Sérgio M.; Degaspari, Nilton; Araújo, Solange Maria S. S. de (Pesquisa Agropecuaria Brasileira, 2014)
This assay was carried out at the Laboratório de Controle Biológico do IAA/PANALSUCAR, Coordonadoria Regional - Sul, Araras, SP, Brazil, and its objective was to know some biological parameters and the intraspecific competition of the tachinid flies, Metagonistylum minense Towns., 1927 and Paratheresia claripalpis Wulp, 1896, both parasitoids of the sugarcane borer Diatraea saccharalis (Fabr., 1794). One thousand inoculations with five replications were made for 200 larvae, aiming to observe the biology of these tachinids. The mean larval period for M. minense was 8.49 days and the weight of single pupae (one maggot per larva) was 39.53 mg. The mean larval period for P. claripalpis was 10.48 days and the mean weight of single pupae was 53.73 mg. For the intraspecific competition between these species it was observed that it is significant in P. claripalpis, where the weight of triple pupae was about 50.94% lower than the weight of single pupae whereas for M. minense this reduction was about 42.73%. The mean number of maggots obtained per female for P. claripalpis was 374.46 ± 22.61 and 438.86 ± 22.35 for M. minense.